1998
DOI: 10.1136/thx.53.10.857
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery pressure variation in patients with connective tissue disease: 24 hour ambulatory pulmonary artery pressure monitoring

Abstract: Background-The specific contribution of secondary pulmonary hypertension to the morbidity and mortality of patients with underlying lung disease can be diYcult to assess from single measurements of pulmonary artery pressure. We have studied patients with secondary pulmonary hypertension using an ambulatory system for measuring continuous pulmonary artery pressure (PAP). We chose to study patients with connective tissue disease because they represent a group at high risk of pulmonary vascular disease, but with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 9 publications
1
44
1
1
Order By: Relevance
“…Again this is not surprising and has been shown previously with fluid filled, pulmonary artery catheters [19] though it has been found that this is not always the case in patients with milder degrees of pulmonary hypertension [9]. Pulmonary artery occlusion pressure was not remeasured after exercise if the resting measurement was normal for the reasons previously discussed.…”
Section: Resting Versus Exercise Pulmonary Haemodynamicsmentioning
confidence: 91%
See 2 more Smart Citations
“…Again this is not surprising and has been shown previously with fluid filled, pulmonary artery catheters [19] though it has been found that this is not always the case in patients with milder degrees of pulmonary hypertension [9]. Pulmonary artery occlusion pressure was not remeasured after exercise if the resting measurement was normal for the reasons previously discussed.…”
Section: Resting Versus Exercise Pulmonary Haemodynamicsmentioning
confidence: 91%
“…The recorder is worn over the patient's shoulder and is lightweight and compact (weighing 650 g and measuring 1883137345 mm) and is described fully elsewhere [9].…”
Section: Pulmonary Artery Pressure Data Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pulsatile pressures in the range of 60/20 mmHg occur at the level of the human pulmonary artery during primary pulmonary hypertension (14) as well as pulmonary hypertension secondary to connective tissue disease (20); these pathological conditions are associated with pulmonary vessel remodeling (10), intimal hyperplasia (21), as well as dysregulated endothelial growth (3) and gene expression (27) associated with formation of plexiform lesions (resulting from either neoplastic or angiogenic endothelial growth) on the vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodinamik belirteçlerin klinik sonlanımı öngörebileceğini bildiren çalışmalar olduğu gibi, bunun aksini öne sürenler de az değildir. Kawut ve ark.ları IPAH ve bağ dokusu ile ilişkili PAH hastalarında, sağkalımın bağ dokusu ile ilişkili PAH hastalarında daha kötü olmasına rağmen her iki grupta hemodinamik verilerin benzer olduğunu belirtmiştir (35). Miyamoto ve ark.larının yaptığı çalışmada 6DYM ve oPAB arasın-da çok zayıf bir ilişkinin olduğu belirtilmiştir (9).…”
Section: Akut Klinik Bozulmaya Dek Geçen Süre (Akbgs)unclassified